Análise Mensal [Março de 2012] - Pereima, João Basilio; Gomes, Antonio Luiz; Nascimento, Ricardo; Conceição, Ronald (Revista Economia & Tecnologia, 2012)
Artigos: O baixo PIB de 2,7% em 2011 foi fabricado pelo Governo A inflação que não assusta